Messel Pit UNESCO World Heritage Fossil Site in the UNESCO Global Geopark Bergstrasse-Odenwald, Germany – Challenges of Geoscience Popularisation in a Complex Geoheritage Context - Marie-Luise Frey; Pascal Schmitz; Jutta Weber (Geoconservation Research)
Despite its paleontological importance, the Messel Pit was under threat to become a waste disposal site, and its eventual designation as the first Natural World Heritage UNESCO geosite in Germany followed an intense fight in which numerous principles of geoheritage and geoscience popularization were explored. The UNESCO agenda 2030 for sustainable development is the basis of current plans for the future of this extraordinary, unique geosite. The financial frame of the development and special support of the State of Hesse were crucial in establishing a visitor center. This provides a conceptual base for the Messel Pit WHS, through cooperation, exhibitions, guided tours, a variety of digital approaches in media use, leading to geotourism products and marketing activities. The challenge since March 2020 during the Sars-CoV-19 pandemic led to the development of web-based games. The new activities include a portrait series named “Deathly Paradise” and a project series of videos. Collaboration with the UNESCO Global Geopark Bergstrasse-Odenwald is realized in different projects. The importance of long-term collaboration between both UNESCO entities, the geosite and the geopark, provide an international best-practise example.